Kombinasi Alat Berat Menggunakan Metode Simpleks Pada Proyek Pembangunan Gedung Wisata Religi Dan Ruang Terbuka Hijau - Daffa Andriano Allansyah Allansyah (Jurnal Vokasi Teknik Sipil, 2024)
Development is an opportunity to maximize the economy, one of which is in the tourism sector. The tourism sector plays a major role in all regions including Bojonegoto. One of the tourist developments in Bojonegoro is the construction of a mosque, which is a religious tourist destination and rest area in the western region of Bojonegoro Regency. In the construction project of the religious tourism building and green open space, there are several work items that require heavy equipment assistance in the implementation process. Problems with excavator and bulldozer performance can have a major impact on the productivity and cost of construction projects. Excavation and embankment work on the religious tourism building and green open space construction project requires several combinations of heavy equipment to complete. This research aims to identify the potential to increase efficiency, reduce cycle time, or optimize the use of these heavy equipment, and the selection of heavy equipment combinations can save project costs. The research method uses a quantitative method by optimizing the comparison of heavy equipment costs using the simplex method linear program. The results of the research are the optimal and economical alternative for excavation work using 4 units of excavators and 2 units of bulldozers for backfill work. Keywords: Bulldozer, Excavator, Project, Simplex